ANALISIS PENGARUH PENGGUNA INTERNET DAN TRANSAKSI E-COMMERCE TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 2011-2023 - Maduwu, Benyamin; Nopeline, Nancy; Luter Purba, Martin (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
The purpose of this study is to determine how Indonesia's economic growth from 2011 to 2023 is influenced by the number of internet users and the value of e-commerce transactions. The technique used is multiple linear regression analysis. The secondary data used comes from the Central Statistics Agency (BPS), Databoks, and APJII. Eviews 13 was used for data processing. This study found that although the value of e-commerce transactions had a negative and insignificant impact on Indonesia's economic growth between 2011 and 2023, the number of internet users had a positive and significant impact. The coefficient of determination was 0.790914, which means that the independent variable could explain 79.09% of the variance in the dependent variable. The government is expected to simplify licensing so that investors are interested in investing in telecommunications and e-commerce development and to tighten regulations on imported goods, such as limiting prices below $100 and prioritizing domestic products.